Genetic correction of induced pluripotent stem cells from a DFNA36 patient results in morphologic and functional recovery of derived hair cell-like cells - Yi Luo; Kaiwen Wu; Xiaolong Zhang; Hongyang Wang; Qiuju Wang (Stem Cell Research & Therapy, 2024)
Abstract Background TMC1 is one of the most common deafness genes causing DFNA36. Patient-derived human induced pluripotent stem cells (iPSCs) provide an opportunity to modelling diseases. TMC1 p.M418K mutation in human is orthologous to Beethoven mice. Here, we investigated the differentiation, morphology and electrophysiological properties of hair cell-like cells (HC-like cells) derived from DFNA36 patient. Methods Inner ear HC-like cells were induced from iPSCs derived from DFNA36 (TMC1 p.M418K) patient (M+/−), normal control (M+/+) and genetic corrected iPSCs (M+/C). Immunofluorescence, scanning electron microscopy and whole-cell patch-clamp were used to study the mechanism and influence of TMC1 p.M418K mutation. Results In this study we successfully generated HC-like cells from iPSCs with three different genotypes. HC-like cells from M+/− showed defected morphology of microvilli and physiological properties compared to M+/+. HC-like cells from M+/C showed recovery in morphology of microvilli and physiological properties. Conclusions Our results indicate that TMC1 p.M418K mutation didn’t influence inner ear hair cell differentiation but the morphology of microvilli and electrophysiological properties and gene correction induced recovery. CRISPR/Cas9 gene therapy is feasible in human patient with TMC1 p.M418K mutation.